2019
DOI: 10.1016/j.fsigen.2019.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Resolving a 150-year-old paternity case in Mormon history using DTC autosomal DNA testing of distant relatives

Abstract: Although autosomal DNA testing has been available for a number of years, its use to reconstruct genetic profiles of people that lived centuries in the past is relatively recent and there are no published cases where it was employed to verify a kinship relation, likely to be an alleged paternity, that occurred one and a half century ago.DNA testing has already been employed to study the ancestry and posterity of Joseph Smith Jr., founder of the Latter-day Saint (Mormon) movement. Thanks to information found on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Finding appropriate likelihood thresholds, with maximization of this cost/benefit trade-off applies to most statistical evaluations in forensic case work. The segment model has been adopted by all the major direct-to-consumer (DTC) genetic testing companies in different versions 10 and implemented in various freely available tools [31,37,[40][41][42][43][44][45]. Variations of the segment model implement a pre-phasing step whereby the paternal/maternal origin of each allele is determined and used to potentially improve the accurate detection of IBD segments [38].…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations
“…Finding appropriate likelihood thresholds, with maximization of this cost/benefit trade-off applies to most statistical evaluations in forensic case work. The segment model has been adopted by all the major direct-to-consumer (DTC) genetic testing companies in different versions 10 and implemented in various freely available tools [31,37,[40][41][42][43][44][45]. Variations of the segment model implement a pre-phasing step whereby the paternal/maternal origin of each allele is determined and used to potentially improve the accurate detection of IBD segments [38].…”
Section: Tablementioning
confidence: 99%
“…Further, in a forensic setting, marker density cannot necessarily be ensured, for instance due to low quality DNA samples. 10 account for linkage disequilibrium (LD) when SNP numbers increase. Kling showed that the false positive rate (i.e.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of the top hits could be identified from their aliases and/or email addresses. From these individuals, family pedigrees were created using information from sources such as public address registers, ArkivDigital 6 and Riksarkivets digitala forskarsal. 7…”
Section: Database Search and Genealogymentioning
confidence: 99%
“…Investigative genetic genealogy (IGG) or forensic genetic genealogy (FGG) has emerged as a powerful forensic tool to generate crucial leads to identify unknown perpetrators and to identify unknown human remains [1][2][3][4][5][6][7]. IGG includes the use of large genotype data sets, typically including hundreds of thousands of single nucleotide polymorphisms (SNPs), in combination with large public genealogy DNA databases in order to track biological relatives of an unknown donor by matching segments of shared DNA [1,[8][9][10].…”
Section: Introductionmentioning
confidence: 99%